PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KONTEKSTUAL PADA TEMA PEDULI TERHADAP MAKHLUK HIDUP DI KELAS IV SD - DewiYani Marselina; Safrida Napitupulu (Bajang Institute, 2024)
This research aims to produce Contextual-based LKPD that can stimulate students and increase student learning motivation on the theme of caring for living things in class IV elementary school and to determine the feasibility test of Contextual-based LKPD on the theme of caring for living things in class IV elementary school. This research produced a product in the form of a contextual-based Student Worksheet (LKPD) on the theme of caring for living creatures in class IV elementary school. The development model used is the ADDIE development model in the form of analysis, design, development, implementation and evaluation. The learning development model used is the ADDIE development model. The percentage obtained from each validator is 80% material experts, 85% design experts and 85% teacher responses, each of which is included in the valid category. Based on the class teacher response questionnaire distributed to researchers after using the LKPD, it shows that many students are interested in LKPD. This is shown by the average results obtained in the teacher response questionnaire being 96% which is included in the category of very practical to use